Social suffering in the neoliberal age : state power, logics and resistance - Soldatic, Karen; St. Guillaume, Louise (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book provides a rich synthesis of research and theory of nascent and emergent critically engaged work examining changing welfare structures, regimes and technologies and the social suffering that is generated in everyday lives. Using the case-study of Australia to discuss socio-legal re-categorisations, automation of welfare governance, technologies of policy design and delivery, conditionality and systems of penalisation, this book will be of interest to all scholars and students of sociology, critical theory, social policy, social work and disability studies, Indigenous studies and settler colonialism"--
OCLC-licensed vendor bibliographic record.
Keywords: Public welfare -- Australia; Neoliberalism -- Social aspects -- Australia; Australia -- Social conditions; Australia -- Social policy; Australia -- Economic policy; SOCIAL SCIENCE / Human Services; POLITICAL SCIENCE / Public Policy / Social Policy; SOCIAL SCIENCE / Sociology / General